The Effect of Palm Oil Plantation Expansion on Labor Absorption in Tebo Regency - Tajmahal Putri, Sastra; Alamsyah, Zulkifli; Fathoni, Zakky (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This research aims to analyze the effect of oil palm plantation expansion on labor absorption in Tebo Regency. This research was conducted in Tebo Regency with a literature study approach. The data used is secondary data with time series type for the period 2002-2023. The analysis method used is descriptive quantitative analysis and multiple linier regression analysis using Eviews 12 application. The results showed that simultaneously, the variables of production of oil palm plantations and FFB price ratio had a significant effect on labor absorption, including total labor and oil palm plantation subsector labor in Tebo Regency. Partially, the variables of production of oil palm plantations and FFB price ratio each had a positive and significant effect on labor absorption in Tebo Regency.